ANALISIS HUBUNGAN ANTARA TINGKAT KEPATUHAN PENYAMPAIAN SPT TAHUNAN DAN SPT MASA DENGAN PENERIMAAN PAJAK (STUDI KASUS PADA KANTOR PELAYANAN PAJAK JAKARTA PALMERAH) - Deddy Arief Setiawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The tax reform by The Directorate General of Taxation is in obtaining high level of tax compliance, high trust of tax administration and high productivity ofthe taxpayer. The main dimension ofthe tax compliance level of the taxpayer is whether they have submitted their monthly and yearly tax report or not. The goal of this research is to observe tax compliance level in submitting of monthly and yearly tax report that can influence the tax revenue. The basis of the theory is literature, tax regulation and tax laws, opinion from researcher or who was expert in the field of taxation. Method of data analysis are descriptive statistics test and hypothesis test. That hypothesis test used The Correlation of Pearson Product Moment Analysis. Recording to the research there is no the relationship linearly between tax compliance level in submitting of monthly and yearly tax report with the tax revenue.Keywood : Tax Compliance Level in Submitting of Submitting of Monthly and Yearly Tax Report, and Tax Revenue